Smart Traffic Management System using IoT Enabled Technology - Bali, Vikram; Mathur, Sonali; Sharma, Vishnu; Gaur, Dev (2020 2nd International Conference on Advances in Computing, Communication Control and Networking (ICACCCN), 2020)
In current scenario one of the serious concern for people in smart cities such as Delhi, Bangalore, Mumbai, Hyderabad etc. is traffic congestion. This has turned out to be a daily problem in current time. Due to this road congestion accidents in the city have are raised to a great extent so lives lost due to accidents are even more crucial. Due to this congestion on the roads, emergency vehicles such as ambulances, fire-cars and other vehicles cannot reach on time. This results in huge loss of life. To tackle these issues up to a great extent we present a solution in this paper. Through the use of IoT enabled technology we can solve these issues by creating "Green Corridors" for emergency vehicles. This can save their time expansion for reaching the proposed destination and can prevent the loss of human life up to great extent. IoT provides a method to tackle these issues by providing smart and intelligent traffic management system. The system gives emergency vehicles the benefit of green corridor and reach destination on time. The RFID reader scans the RFID tag applied on the ambulance and updates the upcoming traffic light to switch to green and displays a message to vehicles ahead of ambulance to provide a "Green Corridor" by shifting other lanes. This system comprises whole traffic system and functions for emergency situations in order to reach the destination without any delay.